(untitled) (Training and Practice : Journal of Educational Sciences, 2021)
In Hungary, since the change of regime in 1990 the church institutes, involving kindergartens, have been allowed to work again. It is gratifying that their numbers are growing. However, the increasing number of children and kindergarten teachers raises new questions regarding methodology and educational issues. The training of religion teachers in the field of theology is focusing on the scholars’ age groups, while the training of early childhood and kindergarten teachers concentrates on the secular nurseries and kindergartens. A particular challenge of our age is how to train educational and theological specialists for the religious institutions while picking up the thread of methodology disrupted and overshadowed in 1945. This essay is looking for the answers for these questions while presenting Religious Education (RE) specialisation and the pedagogical professional examination training, which have been implemented recently at Benedek Elek Faculty of Pedagogy at the University of Sopron.